2023
DOI: 10.1002/dad2.12419
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of hippocampal subfields in the relationship between Alzheimer's pathology and memory interference in older adults

Abstract: Introduction:We tested whether Alzheimer's disease (AD) pathology predicts memory deficits in non-demented older adults through its effects on medial temporal lobe (MTL) subregional volume. Methods: Thirty-two, non-demented older adults with cerebrospinal fluid (CSF) (amyloid-beta [Aβ] 42 /Aβ 40 , phosphorylated tau [p-tau] 181 , total tau [t-tau]), positron emission tomography (PET; 18F-florbetapir), high-resolution structural magnetic resonance imaging (MRI), and neuropsychological assessment were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…A recent study by Adams et al (2023) assessed concordance between CSF-based and PET-based Aβ measures with respect to diagnosis of cognition (normal and MCI). The authors showed high concordance between the two measures with high accuracy (0.93 ± 0.13), precision (0.93 ± 0.17), and an overall AUC of 0.92 (±0.16).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study by Adams et al (2023) assessed concordance between CSF-based and PET-based Aβ measures with respect to diagnosis of cognition (normal and MCI). The authors showed high concordance between the two measures with high accuracy (0.93 ± 0.13), precision (0.93 ± 0.17), and an overall AUC of 0.92 (±0.16).…”
Section: Methodsmentioning
confidence: 99%